Historical Continuity and Changes: Understanding the Dynamics of Islamic Education in Indonesia and Malaysia - Saputra, Kurniawan Dwi; Mughni, Fatimah Az Zahra; Zohkarnain, Nur Asyiqin; Dena Sadewa, M Sonata (Universitas Muhammadiyah Magelang, 2022)
Despite having identical demographic composition with the presence of the Muslim majority, the expression of Islam in Indonesia and Malaysia has a different nuance. Islam in Indonesia is more varied and open, while Islam in Malaysia is more centralized and formal. These different expressions must be influenced by the differences of Islamic education in the two countries. This study intends to examine the Islamic education system in Indonesia and Malaysia by describing the history of its development. By referring to library sources, this study conducted a qualitative analysis with the help of Michel Foucault's genealogical theory. With this theory, the author reveals the changes that have occurred throughout the history of Islamic education in Indonesia and Malaysia. This study found that Islamic education in Indonesia and Malaysia departed from the same origin: traditional Islamic learning. Differences begin to emerge when the British government accommodated Islamic education in the vernacular education system in Malaysia, while the Dutch marginalized Islamic education in Indonesia. The Malaysian government further integrated Islamic education into the national education system, while the Indonesian government recognized Islamic education in an independent form outside of state management. As a result, Islamic education in Indonesia has developed adaptively to the temporal challenges by producing diverse forms of education, while Islamic education in Malaysia is stagnating because of the politization. Government policy also influenced this adaptive character where the strict approach of the Dutch colonial government required Islamic boarding schools in Indonesia to be more independent and creative.